Case Report: Dual Checkpoint Inhibition in Advanced Metastatic Osteosarcoma Results in Remission of All Tumor Manifestations—A Report of a Stunning Success in a 37-Year-Old Patient - Sterz, Ulrich; Grube, Matthias; Herr, Wolfgang; Menhart, Karin; Wendl, Christina; Vogelhuber, Martin (Frontiers in Oncology, 2021)
Background Patients with unresectable metastasized osteosarcoma have a poor prognosis. Current treatment options do not offer a chance to cure the disease in this situation. Despite the fact that immunotherapy has expanded its indications continuously over previous years, its use is not yet established in osteosarcoma. There is a lack of randomized controlled studies that could show a significant benefit in this rare tumor entity. So far efficacy of immunotherapy is only reported in individual cases as well as in mouse models. In order to predict a response to immunotherapy, testing for programmed death-ligand 1 (PD-L1) expression, microsatellite instability (MSI) and tumor mutational burden (TMB) can be useful, but status is not yet clear for most cancer entities. Methods Single case study and review of the literature. Case Presentation This report presents the case of a 37-year-old patient with metastatic advanced osteosarcoma, who had no more established options for tumor treatment left. PD-L1 expression in the most recent tumor sample was high (tumor proportion score (TPS) 90%, combined positive score (CPS) 92%) but no MSI could be detected. In an individual therapy attempt an ongoing and profound remission of all tumor manifestations due to four cycles of immunotherapy with ipilimumab and nivolumab was reached. Despite discontinuation of immunotherapy for three months due to therapy-related pneumonitis, remission of all tumor manifestations was ongoing and no detectable relapse in restaging before onset of Nivolumab-maintenance could be observed. Conclusion The present case constitutes the first report of an adult patient with metastasized advanced osteosarcoma who reached a deep remission of disease by immunotherapy with ipilimumab and nivolumab, which continued even though immunotherapy had to be interrupted. To verify whether the high expression of PD-L1, as seen in this patient, is a predictive marker for response to immunotherapy in osteosarcoma, requires further investigation.